Development of Pet Shelter With IoT-based Monitoring System - Ramli, Firdaus; Masnani Mohamed (Evolution in Electrical and Electronic Engineering, 2024)
The increasing demands of contemporary work have led to a rising trend of cats being left alone at home due to their owners' busy schedules. This situation often results in inadvertent neglect of the cats' nutritional needs and well-being. To address this problem, a pet shelter has developed an IoT-based monitoring system aimed at ensuring optimal conditions for food and litter containers, as well as maintaining suitable ambient temperatures. The system addresses the challenge of providing food automatically by estimating the required quantity over a set period, thus extending its duration and alleviating the burden of constant monitoring. Moreover, the implementation of an automated waste separation system for the litter box significantly enhances efficiency, reducing the time investment required for upkeep and enhancing convenience for cat owners. Additionally, the system enables owners to monitor their cats' condition through online footage, promoting comprehensive well-being. Real-time ambient temperature measurements further empower owners to maintain an optimal temperature range for their cats. In conclusion, these advancements in pet care technology benefit both pets and their human caretakers by ensuring optimal conditions and alleviating the challenges associated with caring for cats left alone at home.